2017
DOI: 10.3389/fpls.2017.01336
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of the Aquaporin Gene Family and Transcriptional Responses to Boron Deficiency in Brassica napus

Abstract: Aquaporins (AQPs) are an abundant protein family and play important roles to facilitate small neutral molecule transport across membranes. Oilseed rape (Brassica napus L.) is an important oil crop in China and elsewhere in the world, and is very sensitive to low boron (B) stress. Several AQP family genes have been reported to be involved in B transport across plasma membranes in plants. In this study, a total of 121 full-length AQPs were identified and characterized in B. napus (AC genome), and could be classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 59 publications
1
45
0
Order By: Relevance
“…For Darmor‐bzh NIP s and BOR s the trivial names given by Yuan et al . () and Chen et al . () were used, while for Zhongshuang11 NIP s and BOR s the locus gene identifier name was used.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…For Darmor‐bzh NIP s and BOR s the trivial names given by Yuan et al . () and Chen et al . () were used, while for Zhongshuang11 NIP s and BOR s the locus gene identifier name was used.…”
Section: Resultsmentioning
confidence: 89%
“…Using this growth set‐up, we determined tissue‐ and B‐dependent expression patterns at ≥ BBCH60 to understand when and where NIPs might play a role in floral B transport fluxes. Thereby, we demonstrated that the previously root‐specific defined BnaA02.NIP6;1a isoform (Yuan et al ., ) is actually highly expressed in the inflorescence (Figure b). Moreover, we demonstrated that BnaC05.NIP3;1b, BnaA05.NIP3;1b and NIP7 isoforms are strongly expressed in various inflorescence tissues, including the rachis and the open‐ and closed flowers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Compared to 13 isoforms in humans (Agre & Kozono, 2003), a relatively large number of isoforms are expressed in plants e.g. 35 MIPs in Arabidopsis thaliana (Johanson et al, 2001), 71 in cotton (Park, Scheffler, Bauer, & Campbell, 2010) and even 121 in Brassica napus (Yuan et al, 2017). In vascular plants, MIPs phylogenetically cluster into four to five distinct subfamilies namely the Plasma membrane Intrinsic Proteins (PIPs), Tonoplast Intrinsic Proteins (TIPs), Small basic Intrinsic Proteins (SIPs), Nodulin26-like Intrinsic Proteins (NIPs) and the X-Intrinsic Proteins (XIPs).…”
Section: Introductionmentioning
confidence: 99%